2022
DOI: 10.5144/0256-4947.2022.8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative chest physiotherapy on oxygenation and lung function in cardiac surgery patients: a randomized controlled study

Abstract: BACKGROUND: Postoperative pulmonary complications in patients who undergo open heart surgery are serious life-threatening conditions. Few studies have investigated the potentially beneficial effects of preoperative physiotherapy in patients undergoing cardiac surgery. OBJECTIVES: Assess the effects of preoperative chest physiotherapy on oxygenation and lung function in patients undergoing open heart surgery. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…The recently published work of our group showed supporting findings [42]. Our RCT demonstrated overall significant postoperative improvements in lung function and oxygen saturation in the intervention group compared with the control group.…”
Section: Discussionsupporting
confidence: 86%
“…The recently published work of our group showed supporting findings [42]. Our RCT demonstrated overall significant postoperative improvements in lung function and oxygen saturation in the intervention group compared with the control group.…”
Section: Discussionsupporting
confidence: 86%
“…positive effect on reducing HLOS, supporting this conclusion, multiple clinical trials have demonstrated that preoperative respiratory physiotherapy utilizing various maneuvers is effective in reducing hospitalization for patients undergoing cardiac surgeries. [28][29][30][31]…”
Section: Originalmentioning
confidence: 99%
“…To assess the effect of preoperative home chest physiotherapy program for one week on oxygenation and lung function. Shahood et al (2022) (21) conducted a randomized controlled trial included 100 patients undergoing open heart surgery (46 in the intervention group, 54 in the control group). The primary outcomes were the differences in respiratory function parameters and oxygen saturation.…”
Section: -Randomized Controlled Trialsmentioning
confidence: 99%